Agronomic characteristcs and control of barley root disease, under no-tillage, in rotation with other crops - dos Santos, Henrique Pereira; Reis, Erlei Melo; Lhamby, Julio Cesar Barreneche; Sandini, Itacir (Pesquisa Agropecuaria Brasileira, 1995)
From 1984 to 1993, at the Cooperativa Agrária Mista Entre Rios Ltda., Guarapuava, PR, Brazil, the effects of some crop rotation systems on yield, root disease control, and yield components of barley were assessed. Four rotation systems were studied: 1) monoculture; 2) one winter without barley; 3) two winters without barley; and 4) three winters without barley. The crops grown in Summer were soybean and corn. Both Winter and Summer crops were grown under no-tillage, except in the Winter of 1989, when limestone was applied before planting winter crops. A randomized complete block design, with four replications and plots with 60 m2, was used. The crop rotation was efficient in controlling root diseases of barley. The crop rotation of barley under no-tillage controlled root diseases.
Keywords: Bipolaris sorokiniana; Gaeumannomyces graminis var. tritici